Nitrogen fertilization of paiaguas grass: production and nutrition - Domingues, Alexandre Alves; Marques Santos, Alessandro Jose; Backes, Clarice; Rodrigues, Lucas Matheus; Teodoro, Arthur Gabriel; Bessa, Stephanie Vicente; Ribon, Adriana Aparecida; Giongo, Pedro Rogerio; Grava de Godoy, Leandro Jose [UNESP]; Fernandes de Resende, Cinthya Cristina (Univ Estadual Mato Grosso Sul, 2021)
Nitrogen (N) is a nutrient associated with the development of plant shoots, which makes it a vitally important element for the maintenance and sustainability of pasture. The goal of this study was to evaluate the effects of nitrogen fertilization on the productive and nutritional traits of Urochloa brizantha Paiaguas, as well as the efficiency of digital imaging and the use of a chlorophyll meter in obtaining green color indices. The experiment was conducted in the field on the Escola farm at the State University of Goias, located in Sao Luis de Montes Belos, GO. A randomized-block design with five treatments and four replicates was adopted. Treatments consisted of four N rates (0, 75, 150, 300, and 600 kg ha(-1)) in the form of ammonium sulfate. The grass responded up to the N rate of 374 kg ha(-1) for production-related traits, such as plant height, number of tillers, and shoot dry matter. Maximum dry matter yields were 21,225 and 13,710 kg ha(-1) year(-1) for the first and second cycles, respectively. Both the chlorophyll meter and digital imaging were efficient in indicating plant N nutritional status. Paiaguas grass responds to N similarly to other Urochloa brizantha cultivars.
Keywords: Chlorophyll meter; Digital imaging; Color indices; Ni trogen; Pasture